Isolation of plastic-degrading fungi from landfill and determining the selected plastics biodegradation capability / Priya Mohan - Priya , Mohan (2020)
Polyethylene Terephthalate (PET), Low Density Polyethylene (LDPE) and High Density Polyethylene (HDPE) are the most important polymers used predominantly in present world. Since synthetic polymers hardly undergo degradation and remain in the environment for a very long time, up to 1000 years, these drawbacks increase the percentage of solid wastes in landfill and threaten the environment. To date, Municipal Solid Waste (MSW) landfill is the most favored disposal method especially among the developing countries. The aim of present study is to evaluate the potential of fungus isolated from landfilled plastics to degrade PET, LDPE and HDPE. Besides, effect of different concentrations of the selected inoculum was carried out to investigate the biodegradation of PET, LDPE and HDPE polymers. A total of eight fungi strains were isolated from untreated dumped plastics. In this study, two liquid media (BOD and Bushnell Haas) were used to determine the most desirable broth media by the fungus to perform their degradation activity. The biodegradation of the plastics were confirmed by average radial diameter of fungi colonies and weight loss of the incubated polymers after 30 days of incubation period at 28⁰C. Based on the results obtained, the maximum degradation of mixed plastics (PET, LDPE and HDPE) was attributed to Aspergillus fumigatus (FI 5) strain in both BOD and Bushnell Haas media with an average weight loss of 1.76% and 2.03% respectively. Considering the cost and biodegradability potential of the isolates in the broth media, BOD media was selected over Bushnell Haas media to evaluate the suitability of the media for the fungus to perform the biodegradation activities. On treatment with different concentrations of A. fumigatus, 1% (w/v) inoculum gave highest weight loss for PET plastics (1.5%), while 5% (w/v) noculum showed highest weight loss for LDPE (21.9%) and HDPE (1.31%) films after 30 days of incubation period. The concentrations of inoculum strongly suggest that the factor has a great effect on biodegradation by fungi. Hence, further FTIR analysis was conducted to study the structural changes of the plastic films with maximum reduction in weight loss treated with A. fumigatus. The results showed the potentiality of A. fumigatus to consume these polymers (PET, LDPE and HDPE) as carbon and energy source and the effectiveness of the strains to perform their biodegradation activity can be clearly seen during the optimal condition.